Oxidant signaling for IL-13 gene expression in lung smooth muscle cells() - Bansal, Geetanjali (2012)
The growth of airway and vascular smooth muscle cells occurs in various lung diseases including asthma, chronic obstructive pulmonary disease, bronchopulmonary dysplasia, lymphangioleiomyomatosis, and pulmonary hypertension. While inflammatory responses are critical in these diseases, the relationship between smooth muscle cell growth and inflammatory mediators is poorly understood. The present study demonstrates that PDGF promotes the expression of IL-13 in lung smooth muscle cells through an oxidant signaling mechanism. Treatment of cultured human airway or pulmonary vascular smooth muscle cells with PDGF promotes IL-13 mRNA and protein expression. IL-13 expression is also detected in smooth muscle of airways and pulmonary vessels in allergen-stimulated mice. PDGF activates the proximal 980 bp region of the IL-13 promoter. PDGF-induced IL-13 expression is suppressed by the inhibition of reactive oxygen species signaling such as by NAD(P)H oxidase inhibition, reactive oxygen species scavenging, and metal-chelation. Treatment of cells with hydrogen peroxide as low as 1 μM also promotes IL-13 gene expression. PDGF-induced cell growth is suppressed by the neutralizing antibody against IL-13 as well as by reactive oxygen inhibitors, and recombinant IL-13 promotes the growth of airway smooth muscle cells. These results demonstrate that oxidant signaling activates IL-13 gene transcription in lung smooth muscle cells and that this signaling mechanism regulates cell growth.